Scrapie and Transmissible Mink Encephalopathy: Search for Infectious Nucleic Acid - Marsh, R. F. (1974)
Brain preparations from animals with scrapie or transmissible mink encephalopathy were phenol extracted and examined for the presence of pathogenic nucleic acid. Animals inoculated with various extracts remained healthy, and analysis on 2.6 to 5% polyacrylamide gels failed to detect a difference in extractable RNA species between infected and normal mink brain.